2019
DOI: 10.1111/1365-2664.13329
|View full text |Cite
|
Sign up to set email alerts
|

Have Welsh agri‐environment schemes delivered for focal species? Results from a comprehensive monitoring programme

Abstract: Agri‐environment schemes (AES) have been criticized for being inadequately monitored and for not delivering the expected benefits to nature. Consequently, the Welsh Government funded a comprehensive programme of monitoring of AES between 2009 and 2012. The AES assessment focused on Tir Gofal (which translates as “Land in Care”) but also included the Organic Farming Scheme, and monitoring focused on a range of taxa of conservation importance: arable plants, grassland fungi, bats (six species), butterflies (thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Given that bats are now protected within the European Union and considered to play important roles as bioindicators (Jones, Jacobs, Kunz, Willig, & Racey, 2009) and in pest suppression in agricultural ecosystems (Russo, Bosso, & Ancillotto, 2018), it is crucial to mitigate these negative impacts that directly arise from agricultural intensification (Park, 2015). The restoration, conservation and management of key habitat features in farmland to enhance bat populations have generally been implemented through AESs, yet these prescriptions (excluding organic farming; see Wickramasinghe, Harris, Jones, & Vaughan, 2003) have failed to achieve their objectives (Angell, Langton, MacDonald, Skates, & Haysom, 2019;Fuentes-Montemayor, Goulson, & Park, 2011;MacDonald, Angell, et al, 2019;Taylor & Morecroft, 2009). In England, targeted AESs have been employed to improve conditions for the greater horseshoe bat (Rhinolophus ferrumequinum), a threatened bat species that is strongly associated with farmland (Duvergé & Jones, 2003;Froidevaux, Boughey, Barlow, & Jones, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that bats are now protected within the European Union and considered to play important roles as bioindicators (Jones, Jacobs, Kunz, Willig, & Racey, 2009) and in pest suppression in agricultural ecosystems (Russo, Bosso, & Ancillotto, 2018), it is crucial to mitigate these negative impacts that directly arise from agricultural intensification (Park, 2015). The restoration, conservation and management of key habitat features in farmland to enhance bat populations have generally been implemented through AESs, yet these prescriptions (excluding organic farming; see Wickramasinghe, Harris, Jones, & Vaughan, 2003) have failed to achieve their objectives (Angell, Langton, MacDonald, Skates, & Haysom, 2019;Fuentes-Montemayor, Goulson, & Park, 2011;MacDonald, Angell, et al, 2019;Taylor & Morecroft, 2009). In England, targeted AESs have been employed to improve conditions for the greater horseshoe bat (Rhinolophus ferrumequinum), a threatened bat species that is strongly associated with farmland (Duvergé & Jones, 2003;Froidevaux, Boughey, Barlow, & Jones, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Bright et al, ). However, criticisms include that targeted AESs are expensive and therefore not applicable at broad spatial scales, and that their positive impacts are mostly restricted to a small number of priority species even though there is now evidence that non‐targeted species also benefit from these schemes (Helden et al, ; MacDonald, Angell, et al, ; MacDonald, Cobbold, et al, ; MacDonald, Maniakowski, Cobbold, Grice, & Anderson, ; Wilkinson, Wilson, & Anderson, ). Many targeted schemes crucially lack monitoring that prevents an assessment of their outcomes, and this is especially true for those targeting nocturnal endangered species such as bats (Park, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, doubt has been cast on the effectiveness of AES in delivering desired outcomes (Kleijn & Sutherland, 2003; Norton et al, 2014). Evidence of AES success is mixed and dependent on factors such as starting conditions, focal organism(s), focal habitat, desired public good and the length and intensity of management duration and monitoring (Critchley et al, 2004; MacDonald et al, 2019). While positive outcomes have been found in differing taxa and habitats (Bright et al, 2015; Dadam & Siriwardena, 2019; Keenleyside et al, 2011; MacDonald et al, 2019), others have reported (a) low success (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of AES success is mixed and dependent on factors such as starting conditions, focal organism(s), focal habitat, desired public good and the length and intensity of management duration and monitoring (Critchley et al, 2004; MacDonald et al, 2019). While positive outcomes have been found in differing taxa and habitats (Bright et al, 2015; Dadam & Siriwardena, 2019; Keenleyside et al, 2011; MacDonald et al, 2019), others have reported (a) low success (i.e. maintaining the status quo ); (b) inconclusive effects or (c) lack of sufficient monitoring (Arnott et al, 2018; Critchley et al, 2004; Davey et al, 2010; Kleijn & Sutherland, 2003; Mountford & Smart, 2014; Norton et al, 2014; Staley et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Certain AES aim to encourage wildflowers and pollinating insects specifically, including wildflower strips, seed mixes and hedgerow enrichment, many of which have been shown to benefit plant-pollinator communities (Wood et al 2015). Yet AES remain controversial, often benefiting a limited suite of species (Wood et al 2016; MacDonald et al 2019), with doubts on whether they are truly effective for conservation management on farmland (Ansell et al . 2016; Riley et al .…”
Section: Introductionmentioning
confidence: 99%